2017
DOI: 10.5152/tpa.2014.838
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of negative childhood experiences in three provinces of Turkey

Abstract: The frequencies of negative childhood experiences for the last one year and for the life-long period were determined using ISPCAN child abuse screening tool in Turkey for the first time in three provinces and in such a large population. The frequency of negative childhood experiences related with child abuse and neglect screened were found to be 42%-70% and it was elucidated that we are confronted with a very significant public health problem and adult health risk in these regions of Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 12 publications
2
37
2
2
Order By: Relevance
“…Although widely used to measure CAN data in the US, European countries and other countries in both East and West, these tools have only recently been recognized in Turkey. A Turkish study measuring the negative childhood experiences using the ICAST-C screening tool showed that Turkey is confronted with a very significant health problem, which also presents a potential risk to adults (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although widely used to measure CAN data in the US, European countries and other countries in both East and West, these tools have only recently been recognized in Turkey. A Turkish study measuring the negative childhood experiences using the ICAST-C screening tool showed that Turkey is confronted with a very significant health problem, which also presents a potential risk to adults (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, research suggests that each type of maltreatment has different effects on individuals' development and wellbeing (Brown et al, 2016;Connor, Steingard, Cunningham, & Anderson, 2004). Moreover, although psychological maltreatment is the most common maltreatment form in Turkey (self-reported prevalence range = 50-70%; worldwide prevalence = 36%; Sofuoglu et al, 2014;Stoltenborgh, Bakermans-Kranenburg, Alink, & van IJzendoorn, 2012), few studies have investigated its effects on adolescents' development and wellbeing. Therefore, it is important to examine and understand its effects on mental health and wellbeing from childhood to adulthood.…”
Section: Current Studymentioning
confidence: 99%
“…Although psychological maltreatment is the most common form of maltreatment reported in Turkish society, according to self-report studies (Sofuoglu et al, 2014), few studies have focused on it, mediator or moderator mechanisms, and its outcomes. In particular, we did not come across any longitudinal research in the literature of Turkey.…”
Section: Implications Of Present Studymentioning
confidence: 99%
“…The reaction of the population, social institutions and health profession in, for example, Iran, to a degree in Turkey, in Arabic countries, India or even former Soviet republics bear witness -with a few exceptions -indicates attitudes ranging from little interest in the suffering of victims to a hostile rejection of those affected [6][7][8]. With the global migration in the last decades and the ethnic, religion and national and international conflicts like war and flights in Iraq and Syria the risk of many forms of violence increased [9].…”
Section: Introductionmentioning
confidence: 99%